Measurement of airflow through regulators and real time integrated monitoring - Gillies, A.; Wu, H.; Mayes, T.; Halim, Adrian (Balkema, 2002)
The mathematical modeling of airflow through operating mine regulators is discussed. Results are used in the development of a computerized monitoring and simulation system to provide immediate or real time data on air behavior within each branch within an underground mine ventilation network through linking of sensors to the ventilation network simulation software. Software has been developed to link real time information generated by mine ventilation monitoring sensors into the network program to undertake network simulations and allow interpretation of key system data and operational changes. The outcome of the project is an online system which can report changes in the mine ventilation system, allow causes of changes to be isolated and rectified, improve balancing of available air throughout the mine and dispense with much of the labor used for underground ventilation measurement. The main work activities involved in the research program have involved examination and modeling of regulators, software modification and considerable mine site testing and optimizing activities.